PENGARUH PEMAKAIAN ALAT PELINDUNG DIRI (APD) TERHADAP INFEKSI CACING PADA PEKERJA PENGANGKUT SAMPAH DI DINAS KEBERSIHAN PERTAMANAN DAN PEMAKAMAN KOTA JAMBI - Martini Martini; Yessy Darnas (Universitas Batanghari Jambi, 2015)
Jambi city was categorized as a municipality (population 100,000 s / d 500,000), with an estimated waste generation of 2.75 liters / person / day. Based on the data of population, estimated waste generation is 470 902 inhabitants Jambi City x 2.75 liters / person / day = 1,294,981 liters / day equivalent to 1,295 m3 (equivalent to 518 tons / day).Jambi City Regional Regulation No.05 of 2007, has established a local work unit which services the cleanliness of parks and cemeteries. Among other main task is to carry out waste transportation services. Workers who work on waste transportation services amounted to 163 people.Observations in the field by taking 20 random respondents, the importance of the 14 respondents are not infected with Ascaris lumbricoides, while 5 respondents lumbricoides ascariasis worm infected. The use of personal protective equipment when transporting garbage effect on whether or not infected garbage workers in JambiKata kunci : APD, Sampah, Ascariasis Lumbricoides